Social media, new ICTs and the challenges facing the Zimbabwe democratic process - Mhiripiri, Nhamo Anthony; Mutsvairo, Bruce (IGI Global, 2021)
Social media in its various forms drew international attention to Zimbabwe during the most intense period of the Zimbabwe crisis up to 2008. It is arguable that social media activism was contributory to the current dispensation of Government of National Unity between ZANU PF and the former opposition Movement for Democratic Change. Social media induced revolution and mass rejection of the status quo of the magnitude seen in the Arab Spring might be difficult to replicate in Zimbabwe. A similar revolution with different magnitude but critical results unfolds in Zimbabwe, especially since the disputed 2008 presidential elections and the mayhem that followed. The use of new communication technologies helped publicize extra-legal activities and human rights abuses often blamed on ZANU PF affiliated militia groups and the security forces. International attention has led to diplomatic intervention.